Analysis of the Influence of HRIS and Perceived Usefulness on Employee Performance in MSME's - Arbain (Journal of Business and Management Inaba, 2026)
This research explores how Human Resources Information Systems (HRIS) and the perception of their usefulness affect employee productivity in manufacturing firms, particularly in light of digital transformation and Industry 4.0. The growing use of digital technologies in human resource management prompts companies to enhance efficiency operations, manage their workforce better, and boost employee productivity through interconnected information systems. Nonetheless, the success of HRIS implementation relies not just on the technological framework but also on how employees view the system’s usefulness. This study utilizes the Technology Acceptance Model (TAM) and Resource-Based View (RBV) as its theoretical basis to clarify the connection between HRIS, perceived usefulness, and employee productivity. The research embraced a quantitative explanatory method, involving 35 employees from manufacturing firms chosen via saturated sampling methods. Questionnaires employing a five-point Likert scale were used for data collection, which was subsequently analyzed through multiple linear regression with IBM SPSS Statistics software. The findings reveal that HRIS significantly enhances employee productivity positively by streamlining administrative processes, managing attendance, monitoring performance, and improving work accuracy. Additionally, perceived usefulness has a notable impact on employee productivity, indicating that those who find HRIS advantageous tend to utilize the system more effectively when performing their jobs. Moreover, both HRIS and perceived usefulness account for 40.7% of the variation in employee productivity. This research adds to the existing literature on HRIS and TAM, offering valuable insights for manufacturing firms in crafting effective digital human resource management strategies aimed at promoting sustainable productivity growth.